2022
DOI: 10.3390/bios12060385
|View full text |Cite
|
Sign up to set email alerts
|

Transducer Technologies for Biosensors and Their Wearable Applications

Abstract: The development of new biosensor technologies and their active use as wearable devices have offered mobility and flexibility to conventional western medicine and personal fitness tracking. In the development of biosensors, transducers stand out as the main elements converting the signals sourced from a biological event into a detectable output. Combined with the suitable bio-receptors and the miniaturization of readout electronics, the functionality and design of the transducers play a key role in the construc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(34 citation statements)
references
References 221 publications
0
34
0
Order By: Relevance
“…Biosensing offers several advantages over traditional analytical methods, including rapid and real-time analysis, minimal sample preparation, and the ability to perform on-site or in-field measurements. However, there are some limitations and challenges associated with biosensors, including non-specific binding, interference from the surrounding environment, and fragility [ 10 , 147 , 148 ]. Table 2 lists some transducer mechanisms used in biosensing and their advantages and disadvantages.…”
Section: Biosensing Technologies and Approachesmentioning
confidence: 99%
See 1 more Smart Citation
“…Biosensing offers several advantages over traditional analytical methods, including rapid and real-time analysis, minimal sample preparation, and the ability to perform on-site or in-field measurements. However, there are some limitations and challenges associated with biosensors, including non-specific binding, interference from the surrounding environment, and fragility [ 10 , 147 , 148 ]. Table 2 lists some transducer mechanisms used in biosensing and their advantages and disadvantages.…”
Section: Biosensing Technologies and Approachesmentioning
confidence: 99%
“…Recent advances in biosensor design and fabrication have led to the development of more sensitive, selective, and rapid biosensors with improved detection limits, response times, and specificity [ 148 ]. These advances have been made possible by new materials and fabrication techniques, as well as by the integration of nanotechnology and microfluidics.…”
Section: Biosensing Technologies and Approachesmentioning
confidence: 99%
“…At a fixed voltage, referring to a reference electrode (e.g., Ag/AgCl or calomel), the sensor drives a faradaic current occasioned by any redox reaction(s) that might occur at the surface of the working electrode. The value of the generated redox current is dependent on the concentration of the analyte that is presented in a supporting electrolyte [ 30 ]. The working electrode could be made of or modified with nanomaterials such as carbon-based materials (e.g., graphite, graphene, or carbon nanotubes), noble metals (e.g., gold, platinum, copper), or metal oxide (indium tin oxide (ITO).…”
Section: Electrochemical-based Biosensorsmentioning
confidence: 99%
“…A growing number of research studies that have been reported on analyzing various sweat biomarkers for use in a broad range of clinical diagnostic purposes, including health concerns, nutritional imbalance, drug abuse, and many more [ 1 , 2 , 3 , 4 ], have seen a ten-fold rise in this field, as shown in Figure 1 . However, there are still gaps in the structured content on related SSD applications based on the current existing review articles, such as insufficient information about a few sweat biomarkers, especially hormones, drugs, nicotine, and vitamin C, and inadequate detailed explanation of the respective application concepts related to these biomarkers and a lack of a fundamental response mechanism of chemical sensors that enable users to understand the process of the target analyte’s detection for various sweat compositions [ 5 , 6 , 7 , 8 , 9 , 10 , 11 ]. Despite these limitations, the existing reviews seemed to disregard addressing issues such as an analysis effect formation mixing new and old sweat samples, which can be a daunting challenge for acquiring a high precision in sweat analysis.…”
Section: Introductionmentioning
confidence: 99%